Acupuncture combined with immunotherapy for recurrent and metastatic cervical cancer: a pilot RCT protocol - Wang, Yan; Xie, Yi; Fang, Yuhang; Sui, Bailu; Yuan, Xinhe; Chen, Yu; Zhang, Ying (Frontiers in Oncology, 2026)
BackgroundCervical cancer (CC) is one of the most common malignant tumors in gynecology, posing a serious threat to women’s health. Particularly for the recurrent/metastatic cervical cancer (R/M CC), the available treatment options are limited and often yield suboptimal outcomes. Although the advent of immune checkpoint inhibitors (ICIs) has brought some improvement in the efficacy for R/M CC, low response rates to ICIs remain a significant challenge in the treatment of R/M CC. In recent years, acupuncture has demonstrated certain clinical efficacy in enhancing the immune function of patients with malignant tumors. This study aims to preliminarily explore the efficacy and safety of acupuncture combined with ICIs for R/M CC and providing data support for subsequent large-scale clinical studies.MethodsThe study is designed as a multicenter, open-label, randomized, and controlled clinical trial. A total of 90 eligible participants will be randomly assigned to the experimental group or the control group in a 1:1 ratio. The experimental group will receive the standard therapeutic regimen including ICIs regimen combined with acupuncture, while the control group will receive the standard therapeutic regimen including ICIs alone. Treatment will be discontinued upon completion of four cycles, disease progression, or intolerable toxicity. Follow-up assessments will be scheduled every 12 weeks until patient death, loss to follow-up, or 2 years after randomization. The primary endpoint of this study is the Objective Response Rate (ORR). Secondary endpoints include Progression-Free Survival (PFS), Overall Survival (OS), immune function, and quality of life. Additionally, detailed records of all adverse events (AEs) will be maintained.DiscussionThis study will be the first randomized controlled trial to investigate the efficacy and safety of acupuncture combined with ICIs for R/M CC, aiming to explore the synergistic enhancement of ICIs by acupuncture as an adjuvant therapeutic modality.Clinical trial registrationClinicalTrials.gov, identifier NCT06591078.